Expert Beliefs Regarding Novel Lipid-Based Approaches to Pediatric Intestinal Failure–Associated Liver Disease. (August 2014) - Diamond, Ivan R.; Grant, Robert C.; Feldman, Brian M.; Tomlinson, George A.; Pencharz, Paul B.; Ling, Simon C.; Moore, Aideen M.; Wales, Paul W.
Objective : To determine expert beliefs regarding the probability of intestinal failure–associated liver disease (IFALD) with novel lipid-based approaches (lipid minimization/ω-3 lipids) in managing IFALD to facilitate Bayesian analyses of clinical trials of these therapies. Study Design : Structured interviews were conducted using a validated approach to belief elicitation with 60 intestinal failure (IF) experts from across North America. Participants were asked to estimate, in an average population of infants referred for management of IF with early IFALD, the probability of advanced IFALD at 3 months following referral in each of 3 scenarios: (1) conventional lipid, (2) ω-3 lipids, and (3) lipid minimization. Probability distributions of the risk of advanced IFALD with each strategy were developed. Distributions of the elicited treatment effect for the novel approaches, relative to conventional lipid, were calculated. Results : Median duration of experience of participants managing patients with IF was 8.5 (range, 2–35) years. The median probability of advanced IFALD using conventional lipid was 32.5%; ω-3 lipids, 17.5%; and lipid minimization, 13%. The median of the elicited treatment effects relative to conventional lipid was a relative risk of 0.53 for the ω-3 lipid and 0.45 for lipid minimization. Conclusions : There was consistent expert opinion that the novel lipid-based approaches are superior to conventional therapy, with similar estimates of treatment efficacy for the 2 approaches. The distributions of the elicited treatment effects can be used as prior distributions in Bayesian analyses of clinical trials of these novel strategies.